(3PNjQI GdeYGO aj TQM GdEQTGOs - (3GdSHRGhj, GdSHRGhj, eMeO HGbQ Hf eMeO eDef GdNQGSGfj, J (B1090(3g` (B1679(3es ((3YdGA GdOjf Hf Cejf GdOjf GdWQjMjs)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdWgGQI, Cj gPG cJGH GdWgGQI, hGdcJGH GSe eaQO LeYg cJH HVe GdbGA hSchfgG, hgh aYGd ef GdcJHs
(3BNQgG (B:s
(3BNQgG(B: (3hCeG GdGSJMHGH ajeG HYO GdKdGKI, adYd gPG GdeSJfO jcaj ajg hEf cGf VYjkaG ddeSGeMI (B.. (3GdSfjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B6: 48s
(3GdPQjYI, L(B10: 16s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis